Benefits and risks of sharing genomic data for research: comparing the views of rare disease patients, informal carers and healthcare professionals - Amorim, Mariana (2022)
Assessing public and patients’ expectations and concerns about genomic data sharing is essential to promote adequate data governance and engagement in rare diseases genomics research. This cross-sectional study compared the views of 159 rare disease patients, 478 informal carers and 63 healthcare professionals in Northern Portugal about the benefits and risks of sharing genomic data for research, and its associated factors. The three participant groups expressed significantly different views. The majority of patients (84.3%) and informal carers (87.4%) selected the discovery of a cure for untreatable diseases as the most important benefit. In contrast, most healthcare professionals revealed a preference for the development of new drugs and treatments (71.4%), which was the second most selected benefit by carers (48.3%), especially by the more educated (OR (95% CI): 1.58 (1.07–2.34)). Lack of security and control over information access and the extraction of information exceeding research objectives were the two most often selected risks by patients (72.6% and 50.3%, respectively) and carers (60.0% and 60.6%, respectively). Conversely, professionals were concerned with genomic data being used to discriminate citizens (68.3%), followed by the extraction of information exceeding research objectives (54.0%). The latter risk was more frequently expressed by more educated carers (OR (95% CI): 1.60 (1.06–2.41)) and less by those with blue-collar (OR (95% CI): 0.44 (0.25–0.77) and other occupations (OR (95% CI): 0.44 (0.26–0.74)). Developing communication strategies and consent approaches tailored to participants’ expectations and needs can benefit the inclusiveness of genomics research that is key for patient-centred care.